2007
DOI: 10.1002/bdd.558
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the impact of sarizotan on the pharmacokinetics of levodopa

Abstract: Coadministration of sarizotan with levodopa, in combination with a dopa-decarboxylase inhibitor had no effect on the pharmacokinetics or adverse event profile of levodopa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…After the administration of 100 mg levodopa combined with a dopa decarboxylase inhibitor, the values obtained for C max were next to 1000 ng/ml [1618]. In our study, in the initial situation of patients, the data ranged from 343.1 to 1433.9 ng/ml, so, in some patients the values were similar to that found by other authors and in others it was lower.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…After the administration of 100 mg levodopa combined with a dopa decarboxylase inhibitor, the values obtained for C max were next to 1000 ng/ml [1618]. In our study, in the initial situation of patients, the data ranged from 343.1 to 1433.9 ng/ml, so, in some patients the values were similar to that found by other authors and in others it was lower.…”
Section: Discussionsupporting
confidence: 88%
“…This parameter ranged from 20 to 90 minutes as in other studies [10, 17, 19]. However, the mean AUC value (62.87 μg.min/ml) was slightly lower than that found by other authors using the same dose of levodopa: 98.9 μg.min/ml [16], 99.7 μg.min/ml [18], 117.0 μg.min/ml [17]. …”
Section: Discussionmentioning
confidence: 50%
“…Recently, it has been demonstrated that sarizotan has no effect on the pharmacokinetics of levodopa (Krösser et al 2007). It has been suggested that the antidyskinetic properties of sarizotan could be mediated via its 5-HT 1A agonist action in the motor cortex, reducing the activity of the corticostriatal glutamate pathway (Antonelli et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The 5-HT 1A receptor agonist tandospirone reduced dyskinesia in L-DOPA-treated PD patients [193]. More recently, preclinical and clinical studies suggest that sarizotan, a 5-HT 1A receptor agonist that possesses weak D 3 and D 4 receptor agonist activity, could ameliorate dyskinetic symptoms in association with L-DOPA [194,195].…”
Section: -Ht 1a Receptor Agonists In Pdmentioning
confidence: 99%